Intestinal Epithelial Cell Exosome Launches IL-1β-Mediated Neuron Injury in Sepsis-Associated Encephalopathy - Xi, Shaosong; Wang, Yunguang; Wu, Chenghao; Peng, Weihua; Zhu, Ying; Hu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Gut-microbiota-brain axis links the relationship between intestinal microbiota and Sepsis-associated encephalopathy (SAE). However, the key mediators between them remains unclear. Methods: Memory test was determined by Water maze. Intestinal flora was measured by 16sRNA sequencing. Neurotransmitter was detected by High Performance Liquid Chromatography (HPLC). Histopathology was determined by HE, IF and TUNEL staining. Flow cytometry was employed to determine the proportion of macrophages. Results: Fecal microbiota tansplantation (FMT) relieved hippocampus impairment of SAE rats by inhibiting inflammation cytokines secretion, the expression of IBA-1 and neurotransmitter disturbance, cell apoptosis and autophagy, accompanied by the reduced M1 polarization and M1 pro-inflammation factors produced by macrophages in mesenteric lymph nodes (MLNs). Actually, M1 polarization in SAE rats depended on intestinal epithelial cell (IECs)-derived exosome. GW4869-initiated the inhibition of exosome secretion notably abolished M1 polarization and the secretion of IL-1β. However, GW4869-mediated the improvement of hippocampus impairment was counteracted by the delivery of recombinant IL-1β to hippocampus. Mechanistically, IECs-derived exosome induced the excessive circulating IL-1β produced by CP-R048 macrophages, which subsequently induced damage and apoptosis of hippocampal neurons H19-7 in an autophagy-dependent manner. And re-activation of autophagy facilitates intestinal IL-1β-mediated hippocampal neurons injury. Conclusion: Collectively, intestinal flora disturbance induced the exosome release of IECs, which subsequently caused M1 polarization in MLNs and the accumulation of circulating IL-1β. Circulating IL-1β promoted the damage and apoptosis of neurons in an autophagy dependent manner. Possibly, targeting intestinal flora or IECs-derived exosome contributes to the treatment of SAE.